COMPARATIVE CHARACTERISTICS OF DIFFERENT TYPES OF THYME: THE COMPOSITION, PROPERTIES AND APPLICATION (REVIEW) - O. A. Vinokurova; O. V. Trineeva; A. I. Slivkin (Разработка и регистрация лекарственных средств, 2019)
On the territory of the European part of Russia along with creeping thyme grows about 20 closely related species, which do not differ loggers in nature and are used along with creeping thyme. Analysis of the scientific literature reveals that until recently the study of the chemical composition of herb thyme various kinds main attention was paid to the definition of a very limited set of biochemical parameters characterizing mainly quantitative content of essential oils and their composition, whereas the other biologically active substances. We studied enough. Available information on the composition of biologically active substances is fragmented and, as a rule, reflects the results of short term observation relates to the different geographical areas and received at different times by different methods of analysis, which complicates the comparison of quantitative content of certain compounds. The analysis generally showed sig-nificant similarity in composition of the biologically active substances of various kinds of herb thyme. This allows you to use other types of medicine that grow in different areas, as well as solve the problem of rational use of natural resources and the need to move away from the culture creeping thyme in a limited geography in Russia. A number of studies have shown that informal types of thyme also have a pronounced anti-inflammatory activity. At the same time, essential oil of different kinds of herb thyme composition characterized by individual components, which, along with microscopic features can be used for identification purposes.